Production of highly enantio selective (-)-menthyl butyrate using Candida rugosa lipase immobilized on epoxy-activated supports - Othman, SS; Basri, M; Hussein, MZ; Rahman, MBA; Abd Rahman, RNZ; Salleh, AB; Jasmani, H (Elsevier Sci Ltd, 2024)
Indexed by Scopus